Augmented Reality Fire Safety Application - Sulaiman, Suzreen Liyana (IRC, 2019)
There is lack of awareness about fire safety among the public and research has shown this problem exists despite many trainings have been conducted. This project aims to increase awareness of especially but not limited to, the people in Universiti Teknologi PETRONAS (UTP) about fire safety by examining existing technology used to disseminate fire safety information, developing a mobile application that augment the use of fire safety device, and performing testing of the application in terms of its usefulness. This project applies the augmented reality (AR) technology to simulate how a fire extinguisher works. AR enables virtual objects to be overlaid onto the realworld environment and it can provide user an interactive experience. Analysis of the testing and survey indicates that the application has helped to gain the attention of the participants regarding fire safety. It is recommended to make further improvements on this application so that in the future, using the AR Fire Safety Application can be included as part of HSE training in UTP.